(untitled) (Siddhajyoti Interdisciplinary Journal, 2022)
Hermeneutic phenomenology is popularly used in the field of qualitative research these days. Many people use the term hermeneutic phenomenology but they bring the data random; narrative, descriptive and reflective as well. In the name of essence, researchers have been collecting opinions, feelings, ideas and dreams more than experiences. What actually is to search is not searched. And, what is not to search is searched and given name hermeneutic phenomenology. So, here I am going to elaborate first what phenomenology is and then the difference between hermeneutic phenomenology and other types of phenomenology; especially between hermeneutic phenomenology and transcendent or descriptive phenomenology and, finally the application of hermeneutic phenomenology in thesis writing. From my side, along with descriptions, I am giving much focus on examples as well.